MUC1-Specific Cytotoxic T Lymphocytes in Cancer Therapy: Induction and Challenge. (26th December 2012) - Roulois, David; Grégoire, Marc; Fonteneau, Jean-François
Abstract : MUC1 glycoprotein is often found overexpressed and hypoglycosylated in tumor cells from numerous cancer types. Since its discovery MUC1 has been an attractive target for antitumor immunotherapy. Indeed, in vitro and in vivo experiments have shown T-cell-specific responses against MUC1 in an HLA-restricted and HLA-unrestricted manner, although some animal models have highlighted the possible development of tolerogenic responses against this antigen. These observations permit the development of new T-cell vaccine strategies capable of inducing an MUC1-specific cytotoxic T cell response in cancer patients. Some of these strategies are now being tested in clinical trials against different types of cancer. To date, encouraging clinical responses have been observed with some MUC1 vaccines in phase II/III clinical trials. This paper compiles knowledge regarding MUC1 as a promising tumor antigen for antitumor therapeutic vaccines applicable to numerous cancers. We also summarize the results of MUC1-vaccine-based clinical trials.